2005
DOI: 10.1021/jo050115r
|View full text |Cite
|
Sign up to set email alerts
|

Me2Zn-Mediated Addition of Acetylenes to Aldehydes and Ketones

Abstract: [reaction: see text] Contrary to expectations, commercially available 2 M Me2Zn in toluene is able to promote the addition of phenylacetylene to aldehydes and ketones. This reactivity is determined by a new, unprecedented mechanism, which involves activation of the zinc reagent via coordination with carbonyl substrates that behave "ligand like". Broad scope, high tolerance to functional groups, and a simple procedure make this new method highly interesting for the synthetic chemist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
4

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 37 publications
0
39
0
4
Order By: Relevance
“…2 M) the ligand-free background reaction proceeds readily, and is presumably the cause of the slight decrease in enantioselectivity. [23] Unfortunately, decreasing the catalyst loading further (< 10 mol %) provided lower yield and significantly lower ee (entries 13–14). The optimization of reaction temperature, time, concentration and catalyst loading has enabled the addition of either TMS-acetylene or phenylacetylene to p -anisaldehyde in good yield (>70%) and ee (>70%) with just 10 mol % catalyst loading.…”
Section: Resultsmentioning
confidence: 99%
“…2 M) the ligand-free background reaction proceeds readily, and is presumably the cause of the slight decrease in enantioselectivity. [23] Unfortunately, decreasing the catalyst loading further (< 10 mol %) provided lower yield and significantly lower ee (entries 13–14). The optimization of reaction temperature, time, concentration and catalyst loading has enabled the addition of either TMS-acetylene or phenylacetylene to p -anisaldehyde in good yield (>70%) and ee (>70%) with just 10 mol % catalyst loading.…”
Section: Resultsmentioning
confidence: 99%
“…According to a reported method, [15] a toluene solution of Me 2 Zn (3.75 mL, 4.5 mmol,1.2 m) was added to a toluene (dry, 2 mL) solution of phenylacetylene (0.53 mL, 4.8 mmol) at room temperature under Ar. After the mixture was stirred for 1 h, a toluene (dry, 5 mL) solution of 4-nitrobenzaldehyde (0.453 g, 3.0 mmol) was added dropwise.…”
Section: -(4-nitrophenyl)-3-phenylprop-2-yn-1-ol (1i)mentioning
confidence: 99%
“…General procedure 1 (GP 1): Double alkylation of (1R,2S)-norephedrine (20) The appropriate alkyl halide (5.0 mmol, 1.0 equiv in the case of 1,4-dibromobutane, and 10.0 mmol, 2.0 equiv in the case of the other alkyl halides) and K 2 CO 3 (3.46-6.92 g, 25.0-50.0 mmol, 5.0-10.0 equiv) were added to a solution of (1R,2S)-norephedrine (20, 0.756 g, 5.0 mmol) in CH 3 CN (30 mL). The heterogeneous mixture was heated to reflux and stirred for 24 h. After the reaction was complete according to TLC, the mixture was cooled to RT and the solid K 2 CO 3 was removed by filtration and washed with ethyl acetate (20 mL).…”
Section: Methodsmentioning
confidence: 99%
“…[17,18] Recently, our research group reported that dimethylzinc is able to induce the addition of terminal acetylenes to carbonyl compounds in the absence of any ligand or activator, [19] leading to the formation of (racemic) propargylic alcohols. [20] The same methodology was subsequently extended to the conversion of N-activated imines and ultimately, a Me 2 Zn-promoted one-pot synthesis of propargylic amines was developed, which made use of various aldehydes 1 and o-methoxyaniline as starting materials (Scheme 1). [21] Phenylacetylene (3) was the only alkyne used in that study leading to propargylic amines 4.…”
Section: Introductionmentioning
confidence: 99%